A Postcolonial Framework for Justification and Eco‐Justice. Issue 2 (8th June 2016) - Nunes, John
Abstract: This work proposes a relationship between eco‐justice and justification by grace rooted in a phenomenological approach. The reality of structural sin experienced by persons living in economic poverty on the African continent is interpreted through the lens of Lutheran catechetical ethics. Lives of repentance will lead to incarnational interventions striving for concrete social transformation.